PENERAPAN RAMBU K3 PADA BENGKEL PEMESINAN PROGRAM STUDI PENDIDIKAN TEKNIK MESIN SEBAGAI SARANA MENINGKATKAN KESADARAN MAHASISWA TERHADAP K3 - Rafli Rizky Arief; Yuyun Estriyanto; Herman Saputro (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The purpose of this research is to improve student awareness on health and safety, of students UNS, by implementing health and safety signs. This research is a institutional action research. The research was conducted in two cycles, with each cycle comprising planning, implementation, observation, and reflection. The subject is students of Mechanical Engineering Education of 126 UNS student. The technique of collecting data are observation, questionaire and documentation, and the analysing data are using analytical techniques descriptive and comparative, and critical analysis. The results showed that through the implementation of health and safety signs, can increase students awareness attitudes towards implementing the health and safety in machining workshop. The increasing of students awareness qccurred from pre-cycle to cycle I was done by setting up the health and safety sign in each machining workshop and machine. In cycle I the was an increase of student awareness, although it was not optimal yet. In cycle II the implementation was done by socialize the lecturers and the lectures assistant about the importance of obeying health and safety sign, in order to be delivered to the student in addition. In cyle II the student awarenes increasing rapidly. The conclusion of this research is the implementation of health and safety signs on the machining workshop in mechanical engineering education can increase student awareness of the importance of occupational health and safety.